Expert Perspectives on Detecting Fake News and Misinformation Governance Using Generative Artificial Intelligence in Nigeria: A Qualitative Exploratory Study - Adamkolo Ibrahim; Babatunde Ojebuyi; Titi Fola-Adebayo; Akindeji Makinde; Olayinka Egbokhare; Peter Aborisade; Joyce Olowoniyi; Tayo Eegunlusi; Oluwayemisi Adebomi; Oluchi Okere; Funmilayo Oguntade; Funmilayo Olubode-Sawe; Abimbola Ogunduyile (Feedback International Journal of Communication, 2026)
The rapid spread of misinformation in digital communication environments presents significant challenges to information integrity, particularly in emerging media ecosystems such as Nigeria. Recent developments in generative artificial intelligence (GenAI) have introduced new possibilities for detecting and managing misleading information across digital platforms. This study investigates how generative AI can contribute to governing information integrity within Nigeria’s misinformation ecosystem from a communication perspective. Using an exploratory qualitative approach, the study draws on in-depth interviews with experts in artificial intelligence, machine learning, digital media, and information governance. The findings reveal that generative AI can enhance the monitoring of misinformation by identifying misleading narratives, analyzing persuasive message patterns, tracking the spread of viral content, and supporting real-time verification processes in journalism and fact-checking. However, the study also shows that the effectiveness of AI technologies depends on contextual adaptation, ethical governance, and collaboration among stakeholders. AI systems alone cannot fully address misinformation challenges without the support of media literacy initiatives and institutional communication strategies. The study concludes that generative AI can play a significant role in strengthening information integrity within digital public communication.